Voluntarisme (Filsafat Kehendak) dalam Filsafat Barat - Misnal Munir (Jurnal Filsafat "WISDOM", 2006)
In the long history of Western Philosophy, philosophicalthoughts were dominated by rationalist clan. This rationalist clanposed the mind (to think) as the essence of human-being (CogitoErgo Sum). The opinion of mind as the essence of human-beingwas disagreed by voluntaries philosophers. Most of voluntariesphilosophers explicitly said that the essence of human-being laidon its wish, I wish therefore I exist (Volo Ergo Sum). The thing that became as the main analyses of this writing isfocused on what the modes of wish argued by voluntariesphilosophers. Its reason is wish appeared as a certain element ofhuman-being’s action. Therefore, in the beginning, it is importantto clarify the meaning of voluntarism philosophy, wish as theattendant of rationality (mind), wish as the essence of humanbeing,and finally many kind of voluntarism schools and their main philosophical thoughts will be described. In the conclusion of this writing, it was formulated that the progress of human civilization, according to voluntaries philosopher, could be carried out because of wishes impetus, whereas the purpose of human mind is to form them as reality.